Moral, competence, and status values in youth sports: predictors of attitude to moral decision-making - Syarifatunnisa Syarifatunnisa; Amung Ma'mun; Anira Anira; Nuryadi Nuryadi; Tite Juliantine (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Youth sports values play a critical role in shaping moral decision-making, particularly in sports competition.